Phytochemistry and Biological Activities of Curcuma aeruginosa (Roxb.) - Aprilia Permata Sari; Unang Supratman (Universitas Gadjah Mada, 2022)
Curcuma aeruginosa Roxb. is a stemless, aromatic rhizomatous plant, generally characterized by red corolla lobes, purple calyx, dark purple leaf sheath, purple-brown midrib, and greenish-blue rhizome. This species is usually blooming during the wet and rainy seasons, while the rhizome and leaves have an aromatic odor indicating the presence of volatile constituents. This plant has been used in many traditional medicines as a disinfectant, expectorant, and tonic, including treatment for the wound, diarrhea, dysmenorrhea, fever, coughs, and asthma. This paper aims to provide C. aeruginosa Roxb., summarized data regarding traditional uses, ethnopharmacology, phytochemistry, and pharmacological activities. From 1987 to 2021, about 34 phytochemicals have been isolated, and up to 223 compounds have been detected using Gas Chromatography-Mass Spectrometry. These metabolites differ from flavonoids, terpenoids, steroids, phenanthrenes, and so forth. Furthermore, various investigations demonstrated that the extracts and compounds obtained from the plant possess several pharmacological activities such as anticancer, antioxidant, antimicrobial, anti-dengue, immunostimulant, anthelmintic, anti-inflammatory, antiandrogenic, anti-nociceptive, and antipyretic, as well as uterine relaxant effect. Curcuma aeruginosa Roxb. is a promising medicinal herb and is usually used as oriental traditional medicine by local folks. Therefore, the result supports this plant as a potential source for therapeutic applications and drug development prospects.